Optimization of Mechanical Properties of Bonded Particle Boards Produced From Agricultural Waste Wood Chips - O. Eyide; N. A. Amenaghawon; L. U. Modebe; J. A. Mee (Journal of Applied Sciences and Environmental Management, 2023)
The aim of this research work was to optimize the production of particle boards from agricultural waste (wood chips). The mechanical properties investigated were the modulus of elasticity (MOE) and modulus of rupture (MOR). The production of particle boards was investigated under the following conditions: stacking time (14-21days), resin loading (386-463 g) and amount of agro residue (154-185 g) using Box-Behnken design. Statistically significant models (p<0.05) were developed to represent the relationship between the responses (MOE and MOR) and the independent variables. Both models showed significant fit with experimental data with R2 values of 0.99 and 0.97 respectively. Analysis of variance (ANOVA) results showed that MOE and MOR were influenced by the stacking time, amount of resin and agro residue used. Response surface methodology (RSM) was used to optimize the MOE and MOR and the optimization results showed that the maximum MOE and MOR values of 1114.09N/mm2 and 9.34 N/mm2 were respectively obtained at the optimum production conditions of stacking time, resin loading and amount of agro residue (i.e. 21days, 462.82g and 185.00 g respectively). The particle board produced at the optimized conditions satisfied the American National Standard Institute ANSI/A208.1-1999 specification for general purpose particle boards.